Validação de conteúdo de instrumento para sistematização da assistência de enfermagem a pessoas atendidas em unidades de tratamento ao queimado - Queiroz, Xênia Sheila Barbosa Aguiar (2020)
Introduction: Burns are important causes of morbidity and mortality in the world population. In Brazil, they represent a serious public health problem. Given this complexity, the form of care and treatment can constitute an aggravating and uncertain factor in the patient's recovery. In this context, it is essential to standardize assistance to burn victims, with the use of a tool that guides nursing care in Burn Treatment Units. Objective: To build and validate an instrument for the systematization of nursing care to people treated in Burn Treatment Units. Methodological Path: This is a methodological study carried out between October 2019 and January 2020 in five stages: identification of the empirical indicators of Basic and Social Human Needs present in the burned person and construction of their respective operational definitions; validation of empirical indicators and their operational definitions by experts in the study area; construction of statements of diagnoses, results and nursing interventions based on the International Classification for Nursing Practice; validation of statements of diagnoses, results and nursing interventions for burn victims, by specialists in the field; structuring of the instrument for the systematization of nursing care for the person served in Burn Treatment Units. In the first stage, 113 empirical indicators were surveyed in the literature, of which 89 correspond to psychobiological needs, 21 to psychosocial needs and 03 to psycho-spiritual needs. In the second stage, 13 nurse specialists participated, who evaluated these indicators and their definitions as to relevance, relevance, clarity, and comprehensiveness. For this, the content validation method was used and the Content Validation Index, Kappa coefficient proposed by Fleiss, was applied. This study obtained a favorable opinion under protocol No. 3.624.400. Results: After analysis, 99 empirical indicators were validated, of which 79 comprised psychobiological needs, 18 psychosocial needs and 02 psycho-spiritual needs. As for the statements, 48 diagnoses, 32 results and 107 nursing interventions were validated. Then, an instrument was built for the systematization of nursing care to people treated in Burn Treatment Units. Final considerations: This instrument will make it possible to advance nursing care to the public in question, as it is a pioneer in nursing practice, with reliability due to its validation. It is expected to contribute with other validation studies, in order to ensure more humane and quality assistance.